An innovative resilience approach: Financial self-help groups in contemporary financial landscapes in the Netherlands. (August 2020) - Lehmann, Julie-Marthe; Smets, Peer
This study questions efficiency-driven institutions in the financial sector during and after the financial crisis of 2008. Frustration about inadequately working financial institutions encouraged citizens to employ self-help initiatives reflected in the revival of, for example, financial cooperatives, sharing economies and community currencies. Some of these grassroots initiatives, such as financial self-help groups, are imported by migrants and refugees. Compared to the formal banking system, financial self-help groups claim effectivity and a human face instead of efficiency in operation and management. We look at financial self-help groups among Ethiopians and Ghanaians living in the Netherlands, placing these financial self-help groups within the contemporary financial landscape. Here, diversity instead of a monoculture of banking institutions shows us a way to a more sustainable financial system. Moreover, this article shows that a combination of different kinds of resilience creates possibilities for analysing the dynamics of a kaleidoscope of financial arrangements and institutions.